Veterinary science breakthroughs in research and practice (Medical Information Science Reference, 2018)
"This book contains a compendium of the latest academic material the latest breakthroughs and recent progress in veterinary science. Including innovative studies on laboratory information management systems, animal welfare, and veterinary reform"--Provided by publisher